Serum ferritin, serum LDH and d-dimer in correlation with the outcome in Covid-19. - Dr. J. Hari Kishan; Dr. Karthikeya Byalya; Dr. V. Sharvan Kumar (International Journal of Medical Research and Review, 2021)
BACKGROUND: Early detection of comorbidities, severe patients with SARS-COV-2 and helpful diagnostic tools is very important for individual treatment and helps us in assessing the outcome of moderate to severe patients.METHOD: In our study we have included 108 patients with RT-PCR positive for SARS COV-2 and the samples for D-dimer, Sr. LDH and Sr.ferritin were sent and analyzed.RESULTS: the effect of D-dimer, serum LDH and serum ferritin individually and combinedly showed in our study there was no significant difference between D-dimer and the outcome however there was a significant p-value of <0.001 with serum LDH and the outcome, and p-value of 0.016 with serum ferritin and outcome.CONCLUSIONS: When the markers individually analyzed they showed a significant association between outcome and markers, in elevated O2and normal patients. Mean D dimer, serum ferritin and serum LDH were high among subjects who required NIV and low among subjects who required O2, on Room air and intubated respectively. In hospitalized patients with respiratory distress, we recommend clinicians closely monitor serum ferritin, serum LDH and D-dimer and also other markers of severity, WBC count, lymphocyte count, platelet count, IL-6 as markers for potential progression to critical illness, has been under the study, however our study sample being 108, a study with a larger number of samples required to predict the outcome.